Intestinal perforation after nivolumab immunotherapy for a malignant melanoma: a case report - Koji Yasuda; Toshiaki Tanaka; Soichiro Ishihara; Kensuke Otani; Takeshi Nishikawa; Tomomichi Kiyomatsu; Kazushige Kawai; Keisuke Hata; Hiroaki Nozawa; Yuri Masui; Yukako Shintani; Toshiaki Watanabe (Surgical Case Reports, 2017)
Abstract Background Nivolumab is a monoclonal antibody against programmed death 1 and has become a standard treatment of advanced melanoma because of its durable response and survival benefits. In this report, we present a case of severe intestinal perforation after nivolumab immunotherapy for malignant melanoma. Case presentation A 73-year-old man with stage IV malignant melanoma underwent nivolumab therapy. The patient presented to our hospital because of a progressing abdominal pain. Radiological evaluation revealed evidence of free intraperitoneal air. Therefore, we diagnosed the patient as having an intestinal perforation, which was successfully resolved after surgical treatment. Conclusion Although intestinal perforation after nivolumab immunotherapy is rare, it can be severe and requires early diagnosis and emergency surgery to ensure a favorable prognosis.